Pengaruh Penerapan Green Accounting Terhadap Corporate Social Responsibility di Bank Perkreditan Rakyat Sukawati Pancakanti - Putu Ayu Nandita Dewanti Aderia Putri; Putu Sri Arta Jaya Kusuma (Fakultas Ekonomi Program Studi Akuntansi Universitas 45 Surabaya, 2024)
This research attempts to ascertain how Green Accounting influences Corporate Social Responsibility at BPR Sukawati Pancakanti. This research uses explanatory and quantitative methods. This research involved 55 employees of BPR Sukawati Pancakanti. In this research, data was collected through questionnaires. Next, IBM SPSS Statistics 24 was used for data analysis. The results of the study showed that the use of green accounting greatly enhanced corporate social responsibility, as evidenced by regression test results that were 0.000 < 0.05. Only the impact of integrating green accounting on corporate social responsibility is covered in this study. Therefore, only one branch of the Sukawati Pancakanti People's Credit Bank was the sample and population studied. Therefore, there is an opportunity for other researchers to take up the same theme with a larger sample. It is anticipated that this study will lead to more knowledge about the application of Green Accounting for Corporate Social Responsibility in the future.